Floral diversity and pollination strategies of three rheophytic Schismatoglottideae (Araceae) - Low, S.L.; Wong, Sin Yeng; Ooi, I.H.; Hesse, M.; Stadler, Y.; Schonenberger, J.; Boyce, P.C (German Botanical Society and The Royal Botanical Society of the Netherlands, 2016)
Homoplastic evolution of ‘unique’ morphological characteristics in the Schismatoglottideae many previously used to define genera – prompted this study to compare morphology and function in connection with pollination biology for Aridarum nicolsonii, Phymatarum borneense and Schottarum sarikeense. Aridarum nicolsonii and P. borneense extrude pollen through a pair of horned thecae while S. sarikeense sheds pollen through a pair of pores on the thecae. Floral traits of spathe constriction, presence and movement of sterile structures on the spadix, the comparable role of horned thecae and thecae pores, the presence of stamen-associated calcium oxalate packages, and the timing of odour emission are discussed in the context of their roles in pollinator management. Pollinators for all investigated species were determined to be species of Colocasiomyia (Diptera: Drosophilidae).